Uji Aktivitas Fraksi Diklorometana Ekstrak Metanol Bangle (Zingiber cassumunar Roxb.) sebagai Terapi Komplementer Malaria secara In Vivo (The Activity Test of Dichloromethane Fraction of Bangle (Zingiber cassumunar Roxb.) Methanolic Extract as Complement - Edda Rachmadenawanti; Bagus Hermansyah; Yuli Hermansyah (Pustaka Kesehatan, 2016)
World Malaria Report reported that Malaria threats 40% of world population in six regions and ninety seven endemic countries. This study aimed to investigate the activity of dichloromethane fraction of Bangle as a complementary therapy of malaria in vivo. This was true experimental laboratories study using 28 mice of Balb/c, divided into seven groups. Five treatment groups were given five dose of dichloromethane fraction of Bangle methanolic extracts as imunostimulant before malaria infection and during malaria therapy by combining with malaria standard therapy. K(+) group was given malaria standard therapy. K(-) group was not given any therapy after infection. Inhibition percentage of malaria parasite in K(-) was 0 and K(+) was 24,74%. The treatment group of 0,09 mg/grBW had the highest inhibition percentage, as many as 88,19%. It declined by decreasing dose of fraction. The result of pearson correlation showed very strong correlation (r=0,880). The Ic50 value of dichloromethane fraction of Bangle methanolic extract as a complementary therapy was 0,008 mg/grBW. In conclusion, dichloromethane fraction of Bangle methanolic extract had immunostimulant effect and antimalarial activity in vivo.   Key words: bangle, complementary therapy, inhibition percentage, malaria